An effective and recyclable decolorization method for polysaccharides from Isaria cicadae Miquel by magnetic chitosan microspheres. Issue 5 (24th January 2022) - Yu, Bingbing; Chen, Yao; Zhu, Lijun; Ban, Mengmeng; Yang, Li; Zeng, Yeda; Li, Shijie; Tang, Chunzhi; Zhang, Danyan; Chen, Xiaoqing
Abstract : Magnetic chitosan microspheres synthesized by a microemulsion method have a good decolorization effect on polysaccharides. Abstract : The purpose of this research was to develop an efficient and non-destructive method for decolorizing of polysaccharides extracted from Isaria cicadae Miquel by magnetic chitosan microspheres (MCM). The optimum decolorization parameters were achieved by response surface methodology as follows: the MCM amount was 8.0%, the adsorption temperature was 48 °C, the adsorption time was 82 min and the pH was 7. Under these optimal conditions, the D r %, R r %, and K c were 90.31 ± 0.12%, 95.40 ± 0.11% and 19.66 ± 0.49, respectively. MCM adsorption of pigment molecules was a spontaneous and endothermic process that could be fitted with the pseudo-second-order equation and the Freundlich equation. Besides, the adsorption mechanism could be controlled by multiple-diffusion steps, including film diffusion and intra-particle diffusion. Furthermore, MCM is a recyclable material. Adsorption with MCM is a promising method to remove pigment molecules of polysaccharide, it may replace the traditional decolorization method.